Tanggung Gugat Marketplace Sebagai Penyedia Layanan Dompet Digital (Shopee-Pay) Terhadap Konsumen - Zinnani F.A, Nelly; Suryono, Ahmad (Indonesian Journal Publisher, 2023)
The current growth of information technology and electronic transaction systems can make the information technology industry a superior industry. The use of the internet as a trading medium continues to increase every year. One of the online business media in Indonesia that has started to use it is the Shopee application. Shopee is an online shopping site specifically designed to provide easy, safe and fast shopping with a strong payment system and logistics support. Shopee has several service features that make it easier for Shopee users, one of which is a digital wallet service or referred to in the application as Shopee-pay. In practice, when using this service, problems or errors sometimes arise, the cause of which arises not only from the user himself, but also from the service provider or third party. Such as frequent cases of loss of shopee-pay balances experienced by consumers, causing losses to the parties. consumer. This research aims to find out and understand the responsibility of the marketplace as a provider of digital wallet services (Shopee-pay) towards consumers. This research uses a statutory, case and concept approach with a normative juridical research type. In this case, Shopee as the marketplace is liable because there is an alleged element of intent or negligence which resulted in the loss of Shopee-Pay balance experienced by consumers and this incident fulfills the elements of an unlawful act regulated in Article 1365 of the Civil Code.